KARAKTERISTIK BAHASA LISAN SISWA KELAS 1 SDN PENDEM I MAGETAN DALAM INTERAKSI BELAJAR MENGAJAR TAHUN AJARAN 2013/2014 - Dhika Puspitasari; Yunita Furinawati; Dihtia Rendra Pratama (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
The purpose of this research is : ( 1 ) describe the form of spoken language first gradestudents of SDN Pendem I Magetanin teaching and learning interactions, and ( 2 ) describe the characteristics of spoken language first gradestudents of SDN Pendem I Magetan. The object of this research is the spoken language students in first grade SDN Pendem I Magetanwhen interacting with the teacher in teaching and learning activities. Outcomes of this study that this research will be uploaded in national journals accredited Lentera(State University of Yogyakarta), Journal Pendidikan IKIP PGRI Madiun, and Journal Widyabastra. This study refers to the spoken form of the language description whichincludes the word class, the form of words, and sentence structure. Word class consists of verbs, nouns, adjectives, adverbs, and word tasks. While the form of a word composed of affix words, repeated words, compound words, and acronym. Sentence structure includes six basic sentence patterns. This study used a qualitative descriptive method. Descriptive methods showed that the study presented here is done solely based on the fact that there is or phenomena that are empirically living in speakers. Collecting data in this study using the methods refer to the tapping technique.